Cognitive reappraisal training for parents of children with autism spectrum disorder - Enav, Yael; Hardan, Antonio Y.; Gross, James J. (Frontiers in Psychiatry, 2022)
Parents of children with autism spectrum disorder (ASD) experience higher stress levels than those of typically developing children. The goal of the current study was to examine whether a mentalization-based intervention would enhance parental cognitive reappraisal, an adaptive form of emotion regulation associated with lower levels of stress. Findings from 27 parents who completed a short training indicated an improvement in cognitive reappraisal. In exploratory analyses, two different types of reappraisal were examined. The intervention-related improvement was found mainly with one type of reappraisal, namely reflective reappraisal that consist of cognitive reappraisal with mentalization characteristics. In light of the evidence indicating that high cognitive reappraisal and high reflective functioning are associated with quality caregiving, findings from the current study suggesting that a brief mentalization-based intervention supports ASD parents' cognitive reappraisal with mentalization characteristics are promising and warrant further investigation.